Pengaruh Country Of Origin dan Persepsi Kualitas terhadap Persepsi Nilai pada Produk Telepon Seluler - Eko Aditia Sri Utomo; Sanaji Sanaji (BISMA (Bisnis dan Manajemen), 2018)
AbstractThe this study aimed to examine the effect Country ofOrigin to perceived quality and perceived value. The object is phone customers who visited in World Trade Center (WTC) Surabaya. The sample is 287 respondens. Country of origin has ten indikator s in this research, perceived qualityhas six indikator s in this research, and perceived value has three indikator s. Hypothesis testing is done by path analyze. Research is showed that country of origin effect the perceived quality, perceived quality effect the perceived value, and country of origin do not effect perceived value. This conclution, country of origin indirectly effect the perceived value.